2018
DOI: 10.1063/1.5040159
|View full text |Cite
|
Sign up to set email alerts
|

Circularly polarized terahertz radiation monolithically generated by cylindrical mesas of intrinsic Josephson junctions

Abstract: We report emissions of circular polarized electromagnetic waves from cylindrically shaped mesa structures of the high-temperature superconductor Bi2Sr2CaCu2O8+δ. The frequency range of circularly polarized emission of a cylindrical mesa with notched sides is between 400 and 430 GHz, which is wider than expected by the patch antenna theory. Three maxima recognized in emission intensity are presumably attributed to excitations of fundamental orthogonal modes and circularly polarized modes. Along with the demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Elarabi et al later reported the first experimental demonstration of IJJ THz sources with the emission of CP THz waves, first from a monolithic THz source in which the ellipticity and evolution direction were tuned by the device geometry and voltage [81], and more recently from a cylindrical antenna [82]. Their highest degree of circular polarization (DOCP) from a monolithic IJJ THz emitter was 99.7%, which is considerably higher than that of QCLs [83][84][85].…”
Section: (Iv-iii) Polarization Control Of Ijj Thz Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Elarabi et al later reported the first experimental demonstration of IJJ THz sources with the emission of CP THz waves, first from a monolithic THz source in which the ellipticity and evolution direction were tuned by the device geometry and voltage [81], and more recently from a cylindrical antenna [82]. Their highest degree of circular polarization (DOCP) from a monolithic IJJ THz emitter was 99.7%, which is considerably higher than that of QCLs [83][84][85].…”
Section: (Iv-iii) Polarization Control Of Ijj Thz Sourcesmentioning
confidence: 99%
“…Light emission with an axial ratio (AR), the ratio between the major and minor axes of the fitted polarization ellipse, less than 3 dB was attributed to a CP light. The CP THz wave emissions from these devices were obtained from the excitations of two transverse orthogonal modes along the major and minor diagonals [81,82]. The evolution of the polarization of the truncated-edge square antenna is plotted in Figs.…”
Section: (Iv-iii) Polarization Control Of Ijj Thz Sourcesmentioning
confidence: 99%
“…Efficient and practical components are essential in the terahertz (THz) range (100 GHz-10 THz) including emitters, waveguides, detectors, and receivers [1][2][3][4][5][6][7]. Consequently, between the developed optical technologies and the mature microwave, a frequency gap exists [8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…In such systems, known as intrinsic Josephson junctions (IJJs), the excitation of a Josephson plasma wave along the ab-plane [6,7] induces macroscopic current oscillations on the crystal surface owing to the interplay with the alternating current (AC) Josephson effect and their synchronous oscillations accompanied by the inductive and capacitive couplings among stacked IJJs [8][9][10][11], which combine to cause electromagnetic (EM) radiation into space [12][13][14]. Intensive research has been carried out since 2007 on Josephson plasma emission (JPE) using mesa-structured devices formed from Bi 2 Sr 2 CaCu 2 O 8+δ (Bi2212) single crystals [15][16][17][18][19][20][21][22][23][24], and further research on the possibility of a novel and practical terahertz (THz) source have been reported [25][26][27][28][29][30][31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%